Challenges and Opportunities in Malawian Education: Focusing on Teacher Training - Szeremley, Csaba (Journal of Central and Eastern European African Studies, 2025)
The primary education system in Malawi experienced significant changes, especially since the abolition of school fees in 1994, which resulted in an instant surge in enrolments. However, access improvements have not translated into substantial gains in educational quality. The primary education sector in Malawi is still under constant pressure and facing numerous challenges. The most important factors that need attention are the inadequate infrastructure, high pupil-teacher ratios and the lack of trained teachers. Financial constraints, such as allocating budgets to teacher salaries and inefficiencies in using School Improvement Grants (SIGs), further hinder progress. Systematic challenges are related to expenditure allocations, educational outcomes and service deliveries. Despite these challenges, there are opportunities to improve educational outcomes through targeted interventions. In-service training programs, like the Primary School Improvement Program (PSIP) and Technology-Assisted Learning (TAL), have demonstrated some positive impacts, especially in enhancing teacher practices and learning environments. Practical teacher training and ICT integration catalyse change in a resource-constrained environment. This paper also discusses recommendations for policy reforms, including better allocation of SIGs, optimising teacher deployment, and enhancing community involvement in school decision-making processes to evoke and strengthen ownership and responsibility outside of the school walls. Addressing the comprehensive inefficiencies requires a multifaceted approach that includes greater accountability in resource use, enhanced teacher support, and more equitable resource distribution across urban and rural schools. Recognising and addressing the unique challenges of the different schools in different areas is crucial. Focusing on cost-effective strategies and leveraging partnerships with international donors can also significantly reshape Malawi's education system. Ultimately, improving teacher quality and ensuring effective service delivery is essential for enhancing learning outcomes and addressing the persistent issues in the education sector in Malawi.